2020
DOI: 10.1152/ajprenal.00160.2020
|View full text |Cite
|
Sign up to set email alerts
|

Is the kidney a target of SARS-CoV-2?

Abstract: The new disease produced by severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) represents a major pandemic event nowadays. Since its origin in China in December 2019, there is compelling evidence that novel SARS-CoV-2 is a highly transmissible virus, and it is associated to a broad clinical spectrum going from subclinical presentation to severe respiratory distress and multiorgan failure. Like other coronaviruses, SARS-CoV-2 recognizes human angiotensin-converting enzyme 2 as a cellular receptor that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
173
1
20

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(215 citation statements)
references
References 91 publications
5
173
1
20
Order By: Relevance
“…Meanwhile, another research has shown that the most common kidney abnormalities are subclinical, and acute kidney injury (AKI) is rare (5%) in mild to moderate SARS‐CoV‐2 infection. However, AKI is most common in critically ill patients with COVID‐19 24 . Studies have recently reported that the human kidney is a particular target for SARS‐CoV‐2 infection 23,25,26 and these results might explain the reason for the abnormal kidney indicator found in the present research.…”
Section: Discussionsupporting
confidence: 58%
“…Meanwhile, another research has shown that the most common kidney abnormalities are subclinical, and acute kidney injury (AKI) is rare (5%) in mild to moderate SARS‐CoV‐2 infection. However, AKI is most common in critically ill patients with COVID‐19 24 . Studies have recently reported that the human kidney is a particular target for SARS‐CoV‐2 infection 23,25,26 and these results might explain the reason for the abnormal kidney indicator found in the present research.…”
Section: Discussionsupporting
confidence: 58%
“…Additionally, studies have shown that ACE2 is also expressed in other organs, with high expression in the ileum and kidney, followed by adipocytes, heart, brain stem, small intestine enterocytes, stomach, liver, and vasculature, leading to more possibilities of extrapulmonary manifestations. 7 , 8 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…AKI may develop in response to the inflammatory phase and cytokine storm, and be exacerbated by hypercoagulation, microangiopathy, rhabdomyolysis, acute tubular necrosis, hypoxia, and hypotension [ 8 , 37 ]. Proteinuria may be caused by direct infection of SARS-CoV-2 in podocytes and proximal tubular cells [ 38 ]. Because renal abnormalities are associated with a high risk of in-hospital death and appear to be more prevalent in transplant recipients [ 36 ], serum creatinine and urinalysis should be monitored closely.…”
Section: Tests For Transplant Recipients With Covid-19mentioning
confidence: 99%